Self-Regulation Strategy for Work College Student Online Collaborative - NAVAS GOTOPO, SORATNA VERONICA; PALACIOS NUÑEZ, MADELEINE LOURDES; OLAYA RODRIGUEZ, JORGE LUIS; LARREA MORALES, LILIANA JANET; BARAZORDA PUGA, NANCY (LACCEI, 2024)
In the context of the pandemic, the research addresses the effects of self-regulation in online collaborative learning (ACL) among university students. A quantitative approach with a quasiexperimental design was used, applying ACL pretest and posttest surveys to a control and experimental group. 80 Business Administration students were selected, divided equally between the two groups. The results demonstrate that the application of selfregulation strategies positively influences online collaborative work, strengthening five key dimensions. This study highlights the importance of self-regulation in university virtual environments to enhance collaborative learning